Profesioanalitas Aparatur dalam Penyelenggaraan Pelayanan Publik di Dinas Penanaman Modal Pelayanan Terpadu Satu Pintu Kota Gorontalo - Nur Padillah Sahibuddin; Arifin Tahir; Sri Yulianty Mozin (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
This study aims to determine and analyze the Professionalism of Apparatus in the Implementation of Public Services at the Investment and One-Stop Integrated Services Office of Gorontalo City. Viewed from the aspects of: (1) Competence, (2) Effectiveness, (3) Efficiency, and (4) Responsibility. This research method uses a Qualitative Approach with a Descriptive type. Data collection techniques used in this study are observation, interviews, and documentation. The results of the study indicate that in the competence dimension, the apparatus has had adequate technical capabilities, evidenced by mastery of the OSS system and participation in various training. The effectiveness dimension is also quite good, indicated by the timeliness of service even though sometimes hampered by OSS network disruptions. In the efficiency dimension, services have run optimally through the use of online systems that save time and costs, and received support from the SKM results with a value of 90.17 in the